"Let Us Sing as We Go": Language Origins and the Sung Response of Faith. Issue 1 (22nd May 2017) - Beaton, Rhodora
Abstract : Theological and evolutionary anthropological analysis of the role of song in human and (some) animal communication can help to expand our understanding of the ways that language functions as mediator of the divine-human relationship. This article considers the role of a musical protolanguage in the evolution of human language, demonstrating the connections between contemporary human language and the songs or calls of other animals. Consideration of the broader category of communication in the place traditionally held by a more narrow understanding of language can help to highlight the role that emotion, instinct, and relationality play in the relationship that humans have with God. Such a realization opens the doors to further theological questions about the role of humanity in a suffering creation, the relationship between God and nonhuman creatures, and the role of song in liturgical celebration.